Modeling the Temperature Field in a Drill Under Influence of High-Frequency Current Hardening (Texas Journal of Multidisciplinary Studies, 2022)
The article presents an analysis of the main structural changes associated with temperature changes under the action of surface hardening by high-frequency currents on the drill surface